Emotional intelligence and its relationship to some variables among kindergarten teachers city of Najran - Jafar, Nada Izzeldeen (Journal of Educational and Psychological Sciences, 2025)
The study aimed to identify emotional intelligence its relationship to some variables among kindergarten teachers in the city of Najran. To achieve the objectives of the study, the researcher used the descriptive survey method by applying the emotional intelligence scale consisting of (54) statements distributed over five areas. The study sample consisted of (80) female teachers. They were selected by simple random method by (25%) of the study population. The results showed intelligence among kindergarten teachers was high, and that there were no statistically significant differences at the significance level (0.05) in emotional intelligence among kindergarten teachers due to the variables of academic qualification and experience. The study recommended increasing guidance programs related to the subject of emotional intelligence and its effective role in the educational field.